2017
DOI: 10.5530/pj.2018.1.20
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of Phytochemical Compounds in Syzygium polyanthum Leaves Extracted using Ultrasound-Assisted Method

Abstract: Context:Syzygium polyanthum has been traditionally formulated by the folklore for the treatment of diseases including diarrhea, rheumatism, diabetes mellitus, hypercholesterolemia, hypertension, gastritis and hyperuricemia. Normally, its phytochemicals are always extracted using solvent, maceration and steam distillation methods, but the use of ultrasound-assisted extraction (UAE) method is still not well documented. Aims: This study aims to extract the phytochemical compounds present in S. polyanthum leaves u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 24 publications
(36 reference statements)
0
37
1
6
Order By: Relevance
“…paniculata (AP) is one of the most well-studied medicinal plant, with reports on its chemical constituents (Hossain et al, 2014;Sharma et al, 2012;Srivastava et al, 2004). On the other hand, S. polyanthum (SP), widely used as spices and traditional medicine in Indonesia and Malaysia, has received more attention in recent years and its phytochemical screening has been intensively investigated due to their potentially wider safety margin and useful pharmacological effects (Hassan et al, 2015;Kusuma et al, 2011;Rahim et al, 2018). The Indonesian Traditional Medicine Polyclinic of Dr. Soetomo General Hospital in Surabaya used extract mixture of AP-SP with ratio of 1:1 for T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…paniculata (AP) is one of the most well-studied medicinal plant, with reports on its chemical constituents (Hossain et al, 2014;Sharma et al, 2012;Srivastava et al, 2004). On the other hand, S. polyanthum (SP), widely used as spices and traditional medicine in Indonesia and Malaysia, has received more attention in recent years and its phytochemical screening has been intensively investigated due to their potentially wider safety margin and useful pharmacological effects (Hassan et al, 2015;Kusuma et al, 2011;Rahim et al, 2018). The Indonesian Traditional Medicine Polyclinic of Dr. Soetomo General Hospital in Surabaya used extract mixture of AP-SP with ratio of 1:1 for T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The S. polyanthum ethyl acetate fraction of the leaf extract contained all of the compounds tested for, namely flavonoids, terpenes, alkaloids, saponins, tannins, and glycosides (Table 1). Recent work showed a number of bioactive compounds in the ethyl acetate fraction of the S. polyanthum leaf methanolic extract, including α-pinene, linalool, nerolidol, caryophyllene oxide, farnesol, phytol, squalene, β-tocopherol, α-tocopherol, β-sitosterol, α-humulene, neophytadiene, hentriacontane, and octanal [21].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…The Abd Rahim et al study [21] also reported that the ethyl acetate fraction of the C. rotundus tuber methanolic extract contained glycoside compounds, which were suspected to be the terpenoid iridoid glycoside groups such as 1α-meth-oxy-3β-hydroxy-4α-(3′,4′-dihydroxyphenyl)-1,2,3,4,-tetra-hydronaphthalin and 1α,3β-dihydroxy-4α-(3′,4′dihydrox-yphenyl)-1,2,3,4,-tetrahydronaphthalin or other rotundus side compounds and their isomers that had been reported by another research team [22], although this tentative identification requires confirmation. The presence of flavonoid compounds in the C. rotundus fraction, which we identified, was also reported by Kilani et al [23].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…In the other hand, bay leaf contains flavonoids and glycosides (Ayoub et al, 2013;Abu-Dahab et al, 2014), volatile compounds, potassium, phosphorus and vitamin A activity (Pharthasarathy et al, 2008), flavonoids, triterpenoids, phenols, saponins and tannins (Santoso et al, 2017). Rahim et al (2018) reported that bay leaf contained squalene, phytol, α-pinene, α-tocopherol, β-sitosterol, pyrogallol, and unknown compounds. Santoso et al (2017) compared six medicinal plants to modify meat composition and quality and found that Sauropus androgynus or bay leaves inclusion were more effective than other four medicinal plants (papaya leaf, basil leaf, noni fruit and Moringa leaf).…”
Section: Introductionmentioning
confidence: 99%